2009
DOI: 10.3109/09513590903184068
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of YKL-40 in peritoneal endometriosis

Abstract: YKL-40 is related to severity of peritoneal endometriosis. However why a different expression level of immunohistochemical staining should occur is not known and needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Another parameter analysed in this study was YKL-40, secreted by neutrophils and macrophages in inflamed tissues, which makes it a biomarker of inflammation. However, the first available publication describing studies on YKL-40 concentration in endometriosis was published in 2010, and there is still only sparse information on this subject [43]. Tuten et al [44] reported significantly higher serum YKL-40 concentrations in patients with endometriosis in comparison to the control group, which is in accordance with the observations of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Another parameter analysed in this study was YKL-40, secreted by neutrophils and macrophages in inflamed tissues, which makes it a biomarker of inflammation. However, the first available publication describing studies on YKL-40 concentration in endometriosis was published in 2010, and there is still only sparse information on this subject [43]. Tuten et al [44] reported significantly higher serum YKL-40 concentrations in patients with endometriosis in comparison to the control group, which is in accordance with the observations of this study.…”
Section: Discussionsupporting
confidence: 87%
“…YKL-40 (alternatively called HCgp39 or CHI3L1) is observed in elevated levels for patients with severe asthma [91], cardiovascular disease and diabetes [92], cancer [93], peritoneal endometriosis [94], morbid obesity [95], osteoarthritis [96], and liver fibrosis [97]. The other chi-lectin YKL-39 (or CHI3L2) has been observed up-regulated in osteoarthritic chondrocytes [98] and osteoarthritic cartilage [99].…”
Section: Enzymes Acting On Chitin and Chitosanmentioning
confidence: 99%